2019
DOI: 10.1021/acs.jmedchem.9b01104
|View full text |Cite
|
Sign up to set email alerts
|

Chirality-Driven Mode of Binding of α-Aminophosphonic Acid-Based Allosteric Inhibitors of the Human Farnesyl Pyrophosphate Synthase (hFPPS)

Abstract: Thienopyrimidine-based allosteric inhibitors of the human farnesyl pyrophosphate synthase (hFPPS), characterized by a chiral α-aminophosphonic acid moiety, were synthesized as enantiomerically enriched pairs, and their binding mode was investigated by X-ray crystallography. A general consensus in the binding orientation of all (R)-and (S)-enantiomers was revealed. This finding is a prerequisite for establishing a reliable structure−activity relationship (SAR) model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…These compounds are highly important in the pharmaceutical and agrochemical sectors, as they are key building blocks for the synthesis of biologically active molecules such as P -containing peptides and related compounds. , The configuration at the P , N -disubstituted carbon is essential to trigger the desired biological activity in the final molecules. , Consequently, the development of asymmetric catalytic methodologies for the preparation of both enantiomers of such compounds would be highly desirable. From the different alternatives for their catalytic asymmetric synthesis, , enantioselective hydrogenation (AH) of suitable precursors should be considered an operationally simple and suitable strategy for their preparation . Herein, we describe the asymmetric hydrogenation of an array of structurally diverse N -substituted vinylphosphonates employing rhodium catalysts derived from phosphine–phosphite and other P -ligands.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These compounds are highly important in the pharmaceutical and agrochemical sectors, as they are key building blocks for the synthesis of biologically active molecules such as P -containing peptides and related compounds. , The configuration at the P , N -disubstituted carbon is essential to trigger the desired biological activity in the final molecules. , Consequently, the development of asymmetric catalytic methodologies for the preparation of both enantiomers of such compounds would be highly desirable. From the different alternatives for their catalytic asymmetric synthesis, , enantioselective hydrogenation (AH) of suitable precursors should be considered an operationally simple and suitable strategy for their preparation . Herein, we describe the asymmetric hydrogenation of an array of structurally diverse N -substituted vinylphosphonates employing rhodium catalysts derived from phosphine–phosphite and other P -ligands.…”
supporting
confidence: 92%
“…The preparation of enantioenriched α-aminophosphonic acid derivatives employing enantioselective catalytic methods is still a non-fully developed area of research. These compounds are highly important in the pharmaceutical and agrochemical sectors, as they are key building blocks for the synthesis of biologically active molecules such as P -containing peptides and related compounds. , The configuration at the P , N -disubstituted carbon is essential to trigger the desired biological activity in the final molecules. , Consequently, the development of asymmetric catalytic methodologies for the preparation of both enantiomers of such compounds would be highly desirable. From the different alternatives for their catalytic asymmetric synthesis, , enantioselective hydrogenation (AH) of suitable precursors should be considered an operationally simple and suitable strategy for their preparation .…”
mentioning
confidence: 99%
“…In structural remodeling of the promiscuously binding thienopyrimidine bisphosphonates (e.g., 5d; Figure 7A), truncation of one phosphonate moiety led to a new series of inhibitors that bind exclusively to the allosteric site of the enzyme (e.g., 10a; Figure 9A) (De Schutter et al, 2014;Park et al, 2017a). Further optimization of the monophosphonate compounds identified an analog with nanomolar in vitro potency (10b; Figure 9A) (Feng et al, 2019). Crystallographic studies have revealed how the newly introduced functional groups provide additional contributions to the binding of this compound.…”
Section: Monophosphonate Inhibitors Of Hfppsmentioning
confidence: 99%
“…On the basis of this observation, it was postulated that the phosphonate moiety in some allosteric inhibitors could be removed without significantly affecting their binding affinity for hFPPS (Park et al, 2017a). However, efforts to completely remove the phosphonate moiety has been unsuccessful thus far, while replacing it with another negatively charged group such as a carboxylic acid could be tolerated (Feng et al, 2019). In view of the fact that the allosteric pocket of hFPPS has evolved to bind FPP, a pyrophosphatecontaining molecule, the requirement for a negatively charged functionality in an allosteric inhibitor fully makes sense.…”
Section: Monophosphonate Inhibitors Of Hfppsmentioning
confidence: 99%
“…Examples include allosteric inhibitors of hFPPS ( e.g. , compounds 3–5 ; Figure ) that bind into a well-defined lipophilic pocket near the active site and interfere with the binding of the IPP substrate . Additionally, compounds that block the farnesylation of GTPases by directly inhibiting the farnesyl transferase enzyme (FTase), such as tipifarnib ( 6 ) and lonafarnib ( 7 ), have also been explored as potential antitumor agents (Figure ).…”
Section: Introductionmentioning
confidence: 99%